Improvement of service delivery : the emergence of biometrics technologies in Singapore. - Tan, Charline Kwee Fang. (2008)
This report seeks to explore possible applications of biometric enhanced-services in Singapore and further discuss future challenges that Singapore might face in the widespread adoption of biometrics.